Concerning the stability of BDF methods - Botta, Vanessa Avansini [UNESP]; Meneguette Jr., Messias [UNESP] (AIP Publishing, 2008)
We present an analysis of A0-stability of BDF methods and proof that zero-stable BDF methods are A0-stable using the Schur-Cohn criterion. With this result we have that zero-stable BDF methods are stiffly-stable. © 2008 American Institute of Physics.
Keywords: BDF methods; Characteristic polynomials; Schur-Cohn criterion; Zeros of polynomials